Practical aspects of delivering a small bowel endoscopy service in the UK. Issue 2 (6th March 2015) - Hale, Melissa F; Davison, Carolyn; Panter, Simon; Drew, Kaye; Sanders, David S; Sidhu, Reena; McAlindon, Mark E
Abstract : Capsule endoscopy remains at the forefront of small bowel investigation, offering the only non-invasive means of directly imaging the mucosa of the small bowel. Recommended for the investigation of obscure gastrointestinal bleeding, Crohn's disease, coeliac disease, small bowel tumours and hereditary polyposis syndromes, the uptake of small bowel capsule endoscopy has been widespread in the UK. However, despite a wealth of published literature supporting the utility of capsule endoscopy in clinical practice, there are limited data regarding the actual practical aspects of service delivery, training and quality assurance. In this article, we attempt to address this by considering specific factors that contribute to provision of a high-quality capsule service. The role of formal training, accreditation and quality assurance measures is also discussed.